Successful turning on of MOSAs under very fast transients. Issue 16 (27th July 2018) - Raju, Kannadasan; Prasad, Valsalal
Abstract : There is a general view that metal oxide surge arresters (MOSAs) are not in a position to offer an effective and consistent protection against very fast transient overvoltages (VFTOs). Quite predictably, it portrays MOSA in a poor light. The present sandwiched position of the arrester is mainly due to the combined effects of strong stray and block capacitances existing in an extra high voltage (EHV) network and the characteristic features of the incoming VFTOs. Contrary to this 'popular view', the theoretical performance assessment studies detailed here establish that a successful turnaround in the operation of MOSA under VFTOs is quite achievable. A detailed account of the electromagnetic transients programme (EMTP) and simulation studies performed is given; several oft‐repeated, critical questions are also addressed. Essential measures to shore up the operation of MOSAs under VFTOs have also been brought to the fore. Finally, this study is a culmination of the 'persistent efforts, brings a happy ending to a long pending issue' and paves way for an effective and consistent protection to gas insulated substation (GIS) and its connected equipment against all kinds of life‐threatening overvoltage surges that include VFTOs.